A Comparison of Self-Report and Audiometric Measures of Hearing and Their Associations With Functional Outcomes in Older Adults. (August 2016) - Choi, Janet S.; Betz, Joshua; Deal, Jennifer; Contrera, Kevin J.; Genther, Dane J.; Chen, David S.; Gispen, Fiona E.; Lin, Frank R.
Objective: The aim was to investigate whether associations of hearing impairment (HI) with functional outcomes in older adults differ when using self-report versus pure-tone audiometry.Method: We examined 1, 669 participants ≥70 years in National Health and Examination Survey from 2005-2006 and 2009-2010 whose hearing was assessed by self-report and pure-tone audiometry. We explored functional outcomes associated with audiometric HI (low physical activity, poor physical functioning, and hospitalization).Results: In adjusted models, we found significant associations of audiometric HI with both subjective and objective outcomes (e.g., dichotomous HI with self-reported difficulty in activities of daily living [ADLs], odds ratio [OR] = 1.47, 95% confidence interval [CI] [1.05, 2.06], and low accelerometer-measured physical activity, OR = 2.19, 95% CI [1.11, 4.34]). In contrast, self-reported HI was only associated with subjective outcomes and not with objective outcomes (e.g., dichotomous HI with difficulty in ADLs, OR = 1.63, 95% CI [1.12, 2.38], and low accelerometer-measured physical activity, OR = 0.95, 95% CI [0.66, 1.35]).Discussion: Results using self-reported hearing should not be considered representative of results using audiometry and may provide distinct aspects of HI in older adults.